Coastal resource management program of Brgy. Sto. Niño Sur, Villa, Iloilo City - Bedonia, Allen; Cajocon, Mary Kharmel; Demonteverde, Dawn.; Dy, Harvey; Victoriano, Remia (2003.)
The problem facing coastal resource threatens to undermine many local economies and other factors. We studied the existence of coastal resource management program of the government within the barangay of Sto. Niño Sur in Villa, Iloilo City. This paper aims to know the socio-economic and demographic profile of the barangay, know the support mechanisms available to CRMP, pinpoint various problems and determine the benefits derived by the people in the barangay to CRMP. This would help significantly in understanding the social and economic status of the people in the barangay. The information, data and derived conclusions from this study am to help local government unit in policy making as well as in coastal resource management program planning by synthesizing the welfare of the people in the said area. There were 40 respondents , a fisher folks, barangay officials and people residing near the vicinity of the coastal area has been determined sample. We used questionnaire and at the same time there were personal interviews. The design of the study was a one-shot survey where the group study and observed the current situation of the people mostly fishermen including the barangay officials in the area which are the subject of the study. Finding shows that the people have an idea of any project or program of the government in the coastal that exist in the barangay. They observed that there were no activities undertaken by the barangay to support CRMP. They are unaware of the measures or activities that were initiated by the barangay. Majority did not have any means in order to have access in information about programs or projects existing within the barangay such as CRMP. In this study our recommendation focus more on how to strengthen the participation of the people to the government in promoting development in the coastal area. With the worsening of problems with regards to CRMP that pose threats to the general public, it is vital to both the government and the private sector to work together by sharing resources expertise, and ideals towards continuous participation of the people. A unified participation from all sectors of society is an important element in the paradigm of development.
Research Paper (Mgt 199-Management Research). -- [Iloilo City] : University of the Philippines Visayas-College of Management, March 2003.